Dietary guidance on plant-based meat alternatives for individuals wanting to increase plant protein intake - Messina, Virginia; Guest, Nanci S.; Duncan, Alison M.; Mangels, Ann Reed; Norris, Jack; Ruscigno, Matt; Glenn, Andrea J.; Wolfram, Taylor; Marinangeli, Christopher P. F.; Messina, Mark (Frontiers in Nutrition, 2025)
A new generation of plant-based meat alternatives (PBMAs) has entered the mainstream. These products contain concentrated sources of plant protein and are formulated to mimic the taste and texture of their meat-based counterparts, especially red meat. The increased availability of these products coincides with calls from health agencies to increase the dietary plant-to-animal protein ratio for health and environmental reasons. The role of PBMAs in achieving the goal of consuming more plant protein may be particularly important since consumption of whole plant foods, such as legumes, which includes pulses (e.g., beans, peas and lentils), is unlikely to increase without major public policy initiatives. Nevertheless, there is debate about the healthfulness of PBMAs and about whether the benefits associated with traditional plant-based diets emphasizing whole plant foods apply to PBMAs. These products are heavily processed, often high in sodium, and contain lower levels of compounds (e.g., fiber, resistant starch, polyphenols) typically associated with the benefits of plant-based diets. On the other hand, PBMAs are excellent sources of protein, and many are fortified with nutrients of concern in plant-based diets. Collectively, the evidence suggests that while they may not provide all the benefits of whole legumes, PBMAs have health and environmental advantages over comparable animal-derived foods. For most individuals, a daily serving of a PBMA fits well within the context of an overall healthy diet. Higher intakes may also be compatible with healthy eating, especially for those whose protein and/or calorie needs are increased.